2013
DOI: 10.1149/2.060401jes
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enhanced Corrosion Resistance of Stainless Steel by Sol-Gel Layer-by-Layer Aluminosilicate Thin Coatings

Abstract: In this study, aluminosilicate sol-gel coatings were deposited on Type 430 stainless steel by multiple spin casting cycles. Amorphous aluminosilicate coatings, 65 nm thick, were prepared from precursor solutions with 50, 100, and 500 mmol dm −3 total concentrations of aluminum and silicon species (molar ratio of Al/Si = 1/4) by 10, 5, and 1 spin casting cycles, respectively. Although the obtained coatings had a similar composition with a molar ratio of Al/Si = 25/75, the coatings with increased density were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The advantages and disadvantages of these materials, and the processing methods developed were discussed. Table 2 shows that numerous OIH sol-gel coatings for corrosion applications were developed [30,50,137,[191][192][193][194][195][196][197]. The number of reviews reported, only since 2016, clearly indicates that this field is still under development and is far from reach a matured stage.…”
Section: [138]mentioning
confidence: 99%
“…The advantages and disadvantages of these materials, and the processing methods developed were discussed. Table 2 shows that numerous OIH sol-gel coatings for corrosion applications were developed [30,50,137,[191][192][193][194][195][196][197]. The number of reviews reported, only since 2016, clearly indicates that this field is still under development and is far from reach a matured stage.…”
Section: [138]mentioning
confidence: 99%
“…In many instances, a dry gel needs further thermal treatment to be densified [20]. The sol-gel process versatility allows incorporation of additional components that introduce material's complementary functionalities, such as UV protection [21,22], anti-fouling [23,24], anti-reflection [25][26][27][28][29], moisture resistance [29][30][31][32][33], corrosion and adhesion protection [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53], along with the enhancement of mechanical, thermal, and optical properties, opening a wide range of application in several fields of science. Furthermore, this method allows the control of several experimental conditions leading to a simple sequence that may be tuned to the nature, final shape, and desired function.…”
Section: General Background Of Sol-gel Coatings For Corrosion Mitigationmentioning
confidence: 99%
“…The focus is here on the most interesting group, which are TiO 2 and SiO 2 -TiO 2 sol-gel biomaterials studied by a number of researchers (Li and de Groot 1993;Li et al 1994;Jokinen et al 1998;Peltola et al 2000;Areva et al 2004Areva et al , 2007Advincula et al 2006;Ä€ aritalo et al 2007;Wang et al 2012). However, other successful sol-gel oxide coatings on stainless steel were recently studied, including aluminosilicates (Habazaki et al 2014), ZrO 2 and SiO 2 -ZrO 2 -mixed oxides (Catauro et al 2014a;Śmieszek et al 2014).…”
Section: Tio 2 and Sio 2 -Tio 2 Biomaterials Sol-gel Tio 2 And Sio 2 mentioning
confidence: 99%
“…But sol-gel TiO 2 enhanced the metal resistance to corrosion. Hence, it improved the implant biocompatibility, so that such coated implants are already in application Habazaki et al 2014;Śmieszek et al 2014).…”
Section: Tio 2 and Sio 2 -Tio 2 Biomaterials Sol-gel Tio 2 And Sio 2 mentioning
confidence: 99%